Analysis of the Sanction Imposition for Perpetrators of Environmental Pollution Due to Hazardous Waste in West Cikarang District: A Study of Decision No. 391/pid.b/lh/2019/PNckr - Absori Absori; Yuli Prasetyo Tri Pamungkas; Esmara Sugeng; Rizka Rizka; Arief Budiono; Moh Indra Bangsawan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This paper aims to analyze the imposition of sanctions for perpetrators of environmental pollution due to hazardous and toxic waste in West Cikarang District, Bekasi Regency, Indonesia. It was based on the enactment of the Republic of Indonesia's Law No. 32 of 2009 on Environmental Protection and Management. The research problems are: 1) How does the government apply criminal sanctions for the perpetrators of environmental pollution due to hazardous and toxic waste in West Cikarang District?; 2) What factors hinder the application of criminal sanctions related to hazardous and toxic waste in West Cikarang District and what efforts have been carried out to resolve such challenges?; and 3) What is the concept of criminal sanction application for perpetrators of environmental pollution? This paper employed the normative juridical research method, which involves an evaluation of related legal regulations (legislations). The results of this paper showed that: 1) The application of sanctions for perpetrators of environmental pollution due to hazardous and toxic waste in West Cikarang District must be carefully carried out. As a foundation for determining a verdict, judges must use Law No. 32 of 2009 on Environmental Protection and Management as a legal basis; 2) Some challenges or hindrances include the lack of legal certainty related to limitations in categorizing the types of committed actions and the yielded impacts; and 3) The process of criminal sanction imposition involves a series of actions that are planned to make sure that the perpetrators are responsible for their actions.